A study on homestay Malaysia: ICT applications - Miraz, Mahadi Hasan; Ramli, Razamin; Ku-Mahamud, Ku Ruhana; Albarune, Abu Raihan Bhuiyan; Islam, Foazul (2015)
Home Stay Tourism is an emerging concept of tourism developed in recent years in the world of tourism as well in Malaysia.It is a model of life for multiple possible aspects. Natural source, heritage wealth, social parameters, friendly hospitality and many other unexplored treasures of dreams for tourism experts.Homestay tourism cannot thrive without the convergence of the needs of the rich and the poor based on the principle of demand mechanism, since it is a key concept in need. Malaysia can exploit the advantage of the potential of tourism endemic in rural areas, where government programs for the poor.This form of tourism is based on three aspects, namely, services, facilities and attractions.Malaysia has a strong position in traction, and unfair.Homestay tourism occurs if home resources and the natural environment is actually cultivated which serve for tourism and preservation. However Promoting tourism largely depends on the active participation of the private sector and the communities where the government's role would is the mediator of that